LEGAL PROTECTION FOR CAPITAL MARKET INVESTORS RELATED TO MUTUAL FUND PURCHASES THROUGH MUTUAL FUND SELLING AGENTS ONLINE - Raphaela Beatrice Thendean (Sean Institute, 2023)
Investment is one aspect of Economic Development in the Long-Term Development Plan (RPJP), one of the indicators in the field. Investment, especially in the Capital Market in Indonesia, can be done in several ways, one of which is through Mutual Funds. Mutual Fund purchases can now also be done online. One of the Investment Manager companies trusted by the public is PT. Emco Asset Management. However, PT. Emco Asset Management went bankrupt, so the investors who invested their funds became concurrent creditors. Investor protection in this matter is needed so that Investor funds that have been invested can still be returned and investors do not lose their rights. The author uses the Normative Juridical research method and refers to Indonesia's prevailing laws and regulations, namely the Financial Services Authority Regulation Number 39/POJK.04/2014 concerning Mutual Fund Selling Agents. In addition, Law Number 8 of 1995 concerning Capital Market and Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations also provide legal protection to Investors. The legal protection provided to investors can be reviewed from several laws and regulations. So in writing this law, the author analyzes the legal protection that online Mutual Fund Investors can receive in preventive protection such as providing transparent and complete information about Mutual Fund Selling Agents and repressive protection in the form of criminal sanctions or administrative sanctions or civil sanctions. With this research, it is hoped that the government will make laws and regulations that are more constricted on online or digital investment, and investors are expected to be wiser in choosing online Mutual Fund Selling Agents to avoid unwanted problems.